“Creación de bancos locales de semillas ancestrales como estrategia para enfrentar el cambio climático”, - Travez Guanotuña, Ximena Dalila (2024)
The project was developed in the Chugchilán and Isinliví parishes with the aim by establishing two seed banks for the traditional plant species conservation, which are suffering genetic erosion, due to climate change and displacement by improved varieties. For carrying out this initiative, it was identified two suitable spaces, what have temperatures between 0 °C to 20 °C and humidity with a maximum reach 50% and were adapted with the appropriate equipment (grain moisture meter, scale, thermo-hygrometer), for the seed conservation, subsequently, it was made the materials on-site collection, which are used by farmers in the agricultural production process, for generating awareness about the native species conservation and the importance establishing seed banks, they were made training for farmers and those are charge each established seed bank. The seed banks established in the Chugchilán parish have dimensions 2.50 meters long, 1.50 meters wide and 1.80 meters high, and in the Isinliví parish with an area 3 x 1.50 meters and a height 2 meters, the size these areas was sufficient to store seeds, by including seed quantity and diversity factors, as well as the samples storage conditions collected in the field. Regarding the made collections, it was got a total 43 samples, which the most notable in the Isinliví area is the 6 types of corn, such as purple, red, black, strawberry, among others, on the other hand, in the Chugchilán area, the 9 types of beans, such as black, yellow nuya, pitaca nuya, green, red, etc., these were stored in the seed bank each location. Finally, they are trained a total 13 farmers and the two representatives from seed banks. This finding reinforces the importance by valuing and preserving autochthonous varieties, not only for their adaptability, but also for their role in the genetic diversity conservation and the food security from communities. Local seed banks guarantee farmers access to these seeds for the next planting season, or as an emergency supply in the crop loss event.